The Sirt1 activator resveratrol improved hematopoiesis in pancytopenia mice induced by irradiation - Xu-Rui Song; Yan-Qiong Cheng; Ding-Feng Su; Ai-Jun Liu (Elsevier, 2019)
Bone marrow failure is a disease syndrome with the disability to produce mature blood cells. Pancytopenia is the most common manifestation of bone marrow failure. Sirt1 is important for the function of hematopoietic stem cells, we hypothesized that Sirt1 activation may improve hematopoiesis. The Sirt1 heterozygous and wild type mice were exposed to lethal 6.5 Gy 60Co-γ rays. The survival time and hematopoietic indexes were evaluated. The survival time of Sirt1 deficiency mice was significantly decreased. The numbers of platelets (PLT), reticulocytes (RET) and white blood cells (WBC) were significantly decreased. C57BL/6 mice were exposed to 6.5 Gy 60Co-γ rays then administrated with resveratrol (20 mg/kg/d) or vehicle. Resveratrol increased the survival time and protective against irradiation induced hematopoietic damage. Resveratrol also significantly increased the numbers of PLT, RET and WBC of mice. It also increased the hematopoietic area and karyocytes number. In HEK293T cells, the expression of LKB1 was significantly increased in cytoplasm but not in nuclei when treated with resveratrol (50 μM). These results suggest that Sirt1 deficiency might aggravate bone marrow failure. Resveratrol corrected this hematopoietic defect and LKB1 might involve in the protective effect on bone marrow failure. Keywords: Resveratrol, Pancytopenia, Sirt1, LKB1, Irradiation